Inequality : a contemporary approach to race, class, and gender - Keister, Lisa A., 1968-; Southgate, Darby E., 1964- (Cambridge, UK. : Cambridge University Press, 2012)
'This textbook is designed to teach undergraduate,and some graduate students about basic concepts and research in the study of social stratification and inequality. Social stratification refers to the unequal distribution of people along measures of well-being such as education, income, and wealth. The book starts with an introduction to theories and research methods used in the field. It then applies those methods to a large number of substantive areas that define the contemporary field of stratification research'--
Includes bibliographical references and index.
Keywords: Social stratification -- United States; Equality -- United States; Social classes -- United States; Wealth -- United States; Poverty -- United States